O biodigestor como alternativa tecnológica para tratamento de dejetos suínos: um estudo de caso do sistema integrado de produção na região das Missões do estado do Rio Grande do Sul - Machado, Rosane Bueno (2011)
Swine breeding is an activity in constant growth in Brazil especially in the Southern regions of Brazil. Nowadays, this activity plays a very relevant role for Brazilian economy, generating employment and income for rural properties. With this in mind, several concerns arise regarding the environmental issue, since the waste resulting from this activity cause great damages to the environment if not treated properly. Based on the factors of this research, the use of the bio-digesters technology is proposed as an alternative for the treatment of the swine breeding waste. A field survey was used as a method, and it was clear that the breeders use some kind of waste treatment technique in their properties in order to ease the issue of environmental contamination. The results of this work show that the breeders are aware of the need for a proper way of dealing with waste and they consider the biodigester as an important piece of technology to be used in their properties. The use of the equipment is beneficial and ranges from pollution control, bio-gas production and bio-fertilizer. Moreover, it is stressed that from the moment the breeders acknowledge the importance of such products and start using them in their properties, there is a considerable cost reduction, increased productivity, and a larger value for money to the swine breeding property.